Geología de los cuadrángulos de Mala, Lunahuaná, Tupe, Conayca, Chincha, Tantará y Castrovirreyna. Hojas: 26-j, 26-k, 26-l, 26-m, 27-k, 27-l, 27-m - [Boletín A 44] - Salazar Díaz, Humberto (1983)
96 p.